2005
DOI: 10.1109/tip.2005.852794
|View full text |Cite
|
Sign up to set email alerts
|

Single quantum dot tracking based on perceptual Grouping using minimal paths in a spatiotemporal volume

Abstract: Abstract-Semiconductor quantum dots (QDs) are new fluorescent probes with great promise for ultrasensitive biological imaging. When detected at the single-molecule level, QD-tagged molecules can be observed and tracked in the membrane of live cells over unprecedented durations. The motion of these individual molecules, recorded in sequences of fluorescence images, can reveal aspects of the dynamics of cellular processes that remain hidden in conventional ensemble imaging. Due to QD complex optical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 41 publications
0
92
0
Order By: Relevance
“…As described previously (Bonneau et al, 2005;Bannai et al, 2006;Ehrensperger et al, 2007), tracking of single QDs, which were identified by their fluorescence intermittence, was performed with MATLAB (MathWorks) using a homemade macro that accounts for blinking in the fluorescence signal. In brief, the method consists of two main steps, applied successively to each frame of the sequence.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously (Bonneau et al, 2005;Bannai et al, 2006;Ehrensperger et al, 2007), tracking of single QDs, which were identified by their fluorescence intermittence, was performed with MATLAB (MathWorks) using a homemade macro that accounts for blinking in the fluorescence signal. In brief, the method consists of two main steps, applied successively to each frame of the sequence.…”
Section: Methodsmentioning
confidence: 99%
“…After detecting candidate particles and linking image feature points frame-byframe, some segmented trajectories are obtained initially. SPT trajectory data from time-lapse TIRF microscopy are combined from individual truncated tracks to create much larger trajectories using a pseudo-three-dimensional volume, and then the track in this pseudo-volume space from each moving particle is obtained using a combination of a minimal energy path approach mediated through a Fast Marching method, 50 a Dynamic Programming approach, 51 and the Linear Assignment Solution. 52 To extract a particle trajectory, our method consists of three modules.…”
Section: Pinpointing Fluorescently-labelled Moleculesmentioning
confidence: 99%
“…When combined with ultrasensitive optical techniques, QDs allow tracking of individual biomolecules in live cells with high signal-to-noise ratio and over unprecedented durations (25)(26)(27). We examined retrograde transport of NGF-containing vesicles by using QD-NGF to mark these organelles.…”
Section: Qd-ngf Is Fully Biologically Activementioning
confidence: 99%